33 A two pronged educational program reduced unwanted hospital admissions by increasing mca compliant personalised care plans in nursing home residents. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Ashworth, Neil; Willis, Derek; Oxenham, David
Abstract : Background: Clinical incident reporting has identified that nursing home residents have been admitted to hospital despite an expressed wish to stay at the nursing home. This may be caused by failures across the whole health system. Previous education has been delivered solely to those with direct patient contact. We were interested to see whether education of policy makers at the same time had extra benefit Aim: To improve the end of life care of nursing home residents and to reduce the unnecessary financial burden to the local health economy, by ensuring a sustainable improvement in the completion, documentation and sharing of personalised care plans. Methods: A longitudinal study of nursing home residents presenting to A and E was conducted over the same 2 week period in October 2016 (n=61) and October 2017 (n=52). Between the two cycles the educational initiative was introduced. This included engaging with senior management in the trust, CCG, ambulance service and clinicians. Results: Pre-intervention; 54.1% (n=33) had an illness suggestive of impaired capacity, but this was not recorded or assessed. Staff asked about the presence of a Personalised Care Plan (PCP) in 16.4% (n=10) of presentations and 4.6% (n=3) had PCP that was adequate enough to guide care. 29.5% (n=18) had a DNACPR form. Post-intervention; There was a 14.8% reduction in A and E presentations. 76.9% (n=40) had an illness suggestive of impaired capacity, with 3.85% (n=2) having a capacity assessment. Staff asked about the presence of a PCP in 19.2% (n=10) of presentations and 9.6% (n=5) had a PCP that was adequate enough to guide care. 53.8% (n=28) had a DNACPR form Discussion: Previous sporadic education yielded a disappointing impact on PCP completion. This study suggests that a two pronged educational approach is more effective.